(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article delves into the fascinating study of German names and surnames, exploring their origins and meanings, as well as their evolution over time. Occupational and geographical influences on names and surnames are examined, along with the significance of pet names and nicknames. From ancient roots to modern-day conventions, this article provides a comprehensive look at the development and cultural significance of German naming traditions.